2021
DOI: 10.1007/s10681-020-02757-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of fiber fineness and yield in ramie (Boehmeria nivea) using SLAF-seq

Abstract: Background Ramie is a major natural fiber crop cultivated in East Asia. The improvement of its fiber yield and fineness are important breeding goals. Fiber yield is a complex quantitative trait comprising ramet number, stem diameter, plant height, skin thickness, and fiber percentage. The fiber fineness is a crucial trait for ramie fiber quality. However, there are few association studies for fiber yield traits and fiber fineness on ramie, and lack high-density SNP maps in natural ramie population. Results Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…KAN2 plays a crucial role in vascular tissue formation, and its loss-of-function mutants cause ectopic xylem and fiber differentiation in amphivasal vascular tissue ( Ilegems et al, 2010 ). Recently, Genome-wide Association Studies (GWAS) analysis identified a significant signal associated with the fiber content of stem barks in ramie, and whole_GLEAN_10016511 was near this signal ( Huang et al, 2021 ). Therefore, whole_GLEAN_10016511 might be the candidate of CF13 and was further examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KAN2 plays a crucial role in vascular tissue formation, and its loss-of-function mutants cause ectopic xylem and fiber differentiation in amphivasal vascular tissue ( Ilegems et al, 2010 ). Recently, Genome-wide Association Studies (GWAS) analysis identified a significant signal associated with the fiber content of stem barks in ramie, and whole_GLEAN_10016511 was near this signal ( Huang et al, 2021 ). Therefore, whole_GLEAN_10016511 might be the candidate of CF13 and was further examined.…”
Section: Resultsmentioning
confidence: 99%
“…The rapid development of next-generation sequencing technology has recently led to the identification of large-scale single-nucleotide polymorphisms (SNPs) in ramie, resulting in several high-density genetic maps ( Liu et al, 2017 ; Zeng et al, 2019 ). Consequently, the genetic architecture of many agronomic traits, such as fiber yield, quality, and flowering time, has been systematically characterized using linkage mapping and genome-wide association mapping ( Zhu et al, 2016 ; Liu et al, 2017 ; Chen et al, 2018 , 2019 ; Zeng et al, 2019 , 2022 ; Huang et al, 2021 ; Wang et al, 2021 ), and several candidates across various loci have been documented ( Liu et al, 2017 ; Wang et al, 2021 ; Zeng et al, 2022 ). Recently, ramie feeding traits have also been researched, and the genetic basis of six forage yield-related traits was characterized, resulting in 78 significant association signals from 43 genomic regions ( Bai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%